Extracellular purines in lung endothelial permeability and pulmonary diseases - Gerasimovskaya, Evgenia; Patil, Rahul S.; Davies, Adrian; Maloney, McKenzie E.; Simon, Liselle; Mohamed, Basmah; Cherian-Shaw, Mary; Verin, Alexander D. (Frontiers in Physiology, 2024)
The purinergic signaling system is an evolutionarily conserved and critical regulatory circuit that maintains homeostatic balance across various organ systems and cell types by providing compensatory responses to diverse pathologies. Despite cardiovascular diseases taking a leading position in human morbidity and mortality worldwide, pulmonary diseases represent significant health concerns as well. The endothelium of both pulmonary and systemic circulation (bronchial vessels) plays a pivotal role in maintaining lung tissue homeostasis by providing an active barrier and modulating adhesion and infiltration of inflammatory cells. However, investigations into purinergic regulation of lung endothelium have remained limited, despite widespread recognition of the role of extracellular nucleotides and adenosine in hypoxic, inflammatory, and immune responses within the pulmonary microenvironment. In this review, we provide an overview of the basic aspects of purinergic signaling in vascular endothelium and highlight recent studies focusing on pulmonary microvascular endothelial cells and endothelial cells from the pulmonary artery vasa vasorum. Through this compilation of research findings, we aim to shed light on the emerging insights into the purinergic modulation of pulmonary endothelial function and its implications for lung health and disease.